Editorial - Tamayo Agudelo, William Fernando (Pensando Psicología, 2013)
We present the new issue of the journal Pensando Psicología, while informing our readers about two very pertinent events, one academic and the other technological. At the academic level, there has been a reorganization of the journal’s scientific and editorial committees (see committee members). Distinguished Colombian and foreign researchers now collaborate in our publications, with the aim of positioning Pensando Psicología as a regional point of reference for scientific dissemination in the fields of clinical and health psychology, educational psychology, social psychology and developmental psychology.